Embedding ecotheology in contextual islamic education: Enhancing students’ eco-literacy through experiential learning - Ayit Irpani; Yani Astuti; Silmi Amrullah (12 Waiheru, 2026)
The aim of this study is to analyze the pedagogical process of instilling ecotheological values in context-based Islamic Religious Education (IRE) learning and to explore its contribution to strengthening students’ ecological literacy within the Islamic school environment. This study responds to the limited integration of ecological values in Islamic educational practices, particularly in connecting Qur’anic teachings on environmental preservation with students’ real-life environmental experiences. Using a qualitative case study approach, the research was conducted at MTs Negeri 11 Tasikmalaya involving IRE teachers and students as participants. Data were collected through classroom observations, semi-structured interviews, and documentation, and analyzed using an interactive analysis model comprising data reduction, data display, and conclusion drawing. The findings indicate that ecotheological values are instilled through the contextualization of Qur’anic teachings on human responsibility toward nature, combined with experiential learning activities grounded in environmental issues affecting the students. This integration not only facilitates students’ conceptual understanding of ecological principles but also encourages the internalization of ecological awareness and environmentally responsible behavior in their daily lives. Contextual learning further creates meaningful learning experiences by connecting religious knowledge with students' authentic environmental realities. This study highlights that integrating ecotheology, contextual learning, and experiential pedagogy contributes to the development of students’ ecological literacy across cognitive, affective, and behavioral dimensions. Therefore, this research demonstrates the importance of innovatively developing Islamic education by positioning ecological values as an integral component of sustainable character education.